Raman Study on Pompeii Potteries: The Role of Calcium Hydroxide on the Surface Treatment - Daniele Chiriu; Pier Carlo Ricci; Andrea Polcaro; Paolo Braconi; David Lanzi; Davide Nadali (Journal of Spectroscopy)
Pottery samples from the Pompeii archaeological site were investigated by IR Raman spectroscopy and EDAX measurements. The analysis of the Raman spectra of the surfaces reveals the presence calcium hydroxide (peak at about 780 cm−1) while the calcium carbonate is totally absent. The comparative studies on the carbonation effect of the surfaces were performed on laboratory grown samples of calcium hydroxide. The samples were treated at high temperature and exposed to different ambient conditions, and the analysis suggests that the original surfaces of Roman pottery were scattered by calcium hydroxide (limewash) before the cooking process in the furnace. The result of this surface treatment not only permits a vitrification of the surfaces but also seems to reduce the content of CO2 in the furnace atmosphere and then obtain a more oxidant ambient during the cooking of the pottery. These results give new insights on the real degree of knowledge of the Romans about the art of ceramics and more generally about chemistry and technologies.